Cr/CrN multilayer coating effect on the surface integrity of Ti-6Al-4V alloy under fatigue loadings - Fernandes, Martin Ferreira [UNESP]; Oliveira Velloso, Verônica Mara De [UNESP]; Cornelis Voorwald, Herman Jacobus [UNESP] (Elsevier, 2022)
Surface treatments are used to improve the tribological properties of titanium alloys for aeronautical applications. The present work aims to investigate the effect of a Cr/CrN multilayer coating on the surface integrity of Ti-6Al-4V alloy under fatigue loadings. SEM, EDS and optical microscopy techniques were applied to characterize the coated surface. The surface integrity after axial fatigue tests of the coated titanium alloy was investigated through SEM of the fracture surfaces. The results showed that cracks nucleated in the brittle layers of CrN during the fatigue cycles and, consequently, reduced the fatigue performance of the Ti-6Al-4V alloy.
Keywords: Cr/CrN multilayer coating; fatigue; surface treatments